1989
DOI: 10.5006/1.3584990
|View full text |Cite
|
Sign up to set email alerts
|

Stress Corrosion Cracking Resistance of 22%Cr Duplex Stainless Steel in Simulated Sour Environments

Abstract: Effect of nickel and nitrogen contents on stress corrosion cracking (SCC) of 22%Cr-3%Mo-base duplex stainless steel was investigated in simulated sour environments with respect to both the base metal and the heat-affected zone (HAZ) of welding. The threshold stress and the critica) chloride concentration for SCC ware evaluated as a function of the ferrite content (a-content) in the alloy. The threshold stress is highest at the a-content of 40 to 45%, and is lowered with decreasing and increasing the a-content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 9 publications
0
13
0
3
Order By: Relevance
“…Ressalta-se que a adição de nitrogênio no gás de proteção no processo GMAW é importante para evitar a perda de nitrogênio, conforme descrito por Westin [10], e por conseqüência a formação excessiva de ferrita em detrimento da austenita. Entretanto para o a soldagem FCAW acredita-se que tal adição não se faz necessária, devido a presença da escória, que ao se solidificar a uma temperatura mais elevada, portanto, primeiro que a poça de fusão, pode atuar como uma barreira à perda de N 2 .…”
Section: Materiais E Métodosunclassified
See 1 more Smart Citation
“…Ressalta-se que a adição de nitrogênio no gás de proteção no processo GMAW é importante para evitar a perda de nitrogênio, conforme descrito por Westin [10], e por conseqüência a formação excessiva de ferrita em detrimento da austenita. Entretanto para o a soldagem FCAW acredita-se que tal adição não se faz necessária, devido a presença da escória, que ao se solidificar a uma temperatura mais elevada, portanto, primeiro que a poça de fusão, pode atuar como uma barreira à perda de N 2 .…”
Section: Materiais E Métodosunclassified
“…As propriedades do metal depositado, como resistência, tenacidade e resistência à corrosão podem ser prejudicadas por um excessivo desvio no balanço de fases com relação ao metal base [9,10].…”
Section: Introductionunclassified
“…[2,7,[9][10][11] Particularly, the importance of nitrogen-containing duplex stainless steels is continuously growing due to their unique advantages. [7,9] Nitrogen alloying, however, offers challenges since the solubility of N in Fe-based alloy is extremely limited at atmospheric pressure, and most of the nitrogen-related research on duplex stainless steel has been performed on the wrought products. [3,[5][6][7]9] At present, a limited number of studies have been reported on cast products of duplex stainless steels, despite their significance in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Recent development of duplex stainless steels occurs mainly in the area of alloying Mo, Cu, N, etc. for further improving mechanical and corrosion properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation